The Xanthomonas type III effector XopAP prevents stomatal closure by interfering with vacuolar acidification. Issue 10 (26th September 2022) - Liu, Longyu; Li, Ying; Xu, Zhengyin; Chen, Huan; Zhang, Jingyi; Manion, Brittany; Liu, Fengquan; Zou, Lifang; Fu, Zheng Qing; Chen, Gongyou
ABSTRACT: Plant stomata close rapidly in response to a rise in the plant hormone abscisic acid (ABA) or salicylic acid (SA) and after recognition of pathogen‐associated molecular patterns (PAMPs). Stomatal closure is the result of vacuolar convolution, ion efflux, and changes in turgor pressure in guard cells. Phytopathogenic bacteria secrete type III effectors (T3Es) that interfere with plant defense mechanisms, causing severe plant disease symptoms. Here, we show that the virulence and infection of Xanthomonas oryzae pv. oryzicola ( Xoc ), which is the causal agent of rice bacterial leaf streak disease, drastically increased in transgenic rice ( Oryza sativa L.) plants overexpressing the Xoc T3E gene XopAP, which encodes a protein annotated as a lipase. We discovered that XopAP binds to phosphatidylinositol 3, 5‐bisphosphate (PtdIns(3, 5)P2 ), a membrane phospholipid that functions in pH control in lysosomes, membrane dynamics, and protein trafficking. XopAP inhibited the acidification of vacuoles by competing with vacuolar H + ‐pyrophosphatase (V‐PPase) for binding to PtdIns(3, 5)P2, leading to stomatal opening. Transgenic rice overexpressing XopAP also showed inhibition of stomatal closure when challenged by Xoc infection and treatment with the PAMP flg22. Moreover, XopAP suppressed flg22‐induced gene expression, reactive oxygen species burst and callose deposition in host plants, demonstrating that XopAP subverts PAMP‐triggered immunity during Xoc infection. Taken together, these findings demonstrate that XopAP overcomes stomatal immunity in plants by binding to lipids. Abstract : The Xanthomonas type III effector XopAP binds to the phosphoinositide PtdIns(3, 5)P2 in the tonoplast and regulates proton transport, interfering with vacuole acidification and leading to stomatal opening for the invasion of pathogens. Moreover, XopAP subverts pathogen‐associated molecular pattern‐triggered immunity during Xanthomonas oryzae pv. oryzicola infection.